Oneiric Cinema Creating a Collective Dream - Junaid, Mahreen (European Journal of Social Science Education and Research, 2024)
Dreams have been a source of inspiration for humans throughout the history. They vary from the ordinary to surreal. They are a universal phenomenon that links the entire humanity. They are visual and spatial experience, but very personalized. Throughout history, many artists and researchers have tried to portray dreams through various mediums such as arts and literature. But the question who success full they were in portray of nocturnal fantasies? This paper aims to present challenges that are inevitable in various mediums for the portray of dreams. It explains how cinema is one such medium that can generate a common dream that is relatable and re-interpretable. This study is to guide researchers in the field of arts and spatial design to help them pick their medium for portraying of dreams to get the most suitable come. It suggests how the cinema screen works as the psychological prosthesis of our dream screen and that the development of film technology has allowed us to view films that very faithfully mimic night fantasies. Thus, the experience of watching films in the cinema is an approximation of our own dreaming experience.